Выявление соотношения функций и процессов при инвестировании в рекреационную сферу в Крыму - Ванюшкин, А.С. (Культура народов Причерноморья, 2014)
В статье на основании анализа деятельности органов исполнительной власти выявлены
функции и процессы, необходимые для привлечения инвестиций в рекреационную сферу, на основании
выявленного перечня функций и процессов построена матрица соответствия функций и процессов
инвестиционной деятельности в рекреационной сфере, в соответствии с концепцией реинжиниринга бизнес-
процессов. У статті на підставі анализу діяльності органів виконавчої влади виявлено функції та процеси,
необхідні для залучення інвестицій в рекреаційну сферу, на підставі виявленого переліку функцій та процесів
сформовано матрицю відповідності функцій та процесів інвестиційної діяльності в рекреаційній сфері,
відповідно до концепції реінжинірингу бізнес-процесів. The functions of various executive bodies and authorities in Crimea, concerning investment process in
recreation sphere were analyzed, as well as tax administration, property fund, antimonopoly service, land resources
committee, architecture and building inspection, sanitary and epidemiological control, state industrial control of labor
conditions, committee on memorials protection; on the basis of this analysis, the basic functions and processes,
necessary while attracting investment into recreation sphere in regional scale, were determined; these functions and
processes concern interaction with leading foreign investors and consultants in order to form positive image of Crimea
and its recreation sphere, determining parameters of privilege tax regime for investors, preparing programs for
separate territories development, as well as infrastructure modernization, giving of land and building permits, tenders
preparing and other; in its turn, basing on the list of functions and processes of attracting investment into recreation
sphere in regional scale, the matrix of correspondence between these functions and processes was formed, according
to the principles of business processes reengineering concept.